KEBEBASAN BERSERIKAT DAN BERKUMPUL DALAM PERSPEKTIF HAK ASASI MANUSIA - Tarmudi, Tarmudi; Widagdo, Gatot Subroto; Putra, Rengga Kusuma; Saragih, Geofani Milthree; Amelia, Risky (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to analyze freedom of association and assembly from a human rights perspective, and explore the challenges faced in its implementation in various countries. The scope of the study includes a review of various cases of violations of the right to freedom of association and assembly, both in countries with democratic and authoritarian systems. In addition, this study will also discuss the role of international organizations and civil society in promoting and protecting these rights. This study will not only discuss the theory and basic principles of freedom of association and assembly, but will also dig deeper into how these rights are implemented in practice, the challenges faced, and steps that can be taken to strengthen the protection of these freedoms throughout the world. This study is expected to make a significant contribution to understanding the complexity of freedom of association and assembly and its impact on human rights as a whole. This study uses a qualitative approach with a case study design. The qualitative approach was chosen because it allows researchers to dig deeper into freedom of association and assembly in the context of Human Rights (HAM).